2018
DOI: 10.1155/2018/3815689
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Chronic Respiratory Symptoms among Pharmaceutical Factory Workers

Abstract: Background Chronic respiratory symptoms including chronic cough, chronic phlegm, wheezing, shortness of breath, and chest pain are manifestations of respiratory problems which are mainly evolved as a result of occupational exposures. This study aims to assess determinants of chronic respiratory symptoms among pharmaceutical factory workers. Methods A case control study was carried out among 453 pharmaceutical factory workers with 151 cases and 302 controls. Data was collected using pretested and structured que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 18 publications
5
25
1
Order By: Relevance
“…According to a case control study by Asfaw et al among pharmaceutical workers of Ethiopia the adjusted odds ratio for previous history of respiratory diseases was 3.36 for the development of chronic respiratory symptoms in the future. 15 The study done by Galobardes et al among the historical cohort of male students who attended Glasgow university between 1948 and 1968 also revealed that a history of bronchitis in early life was moderately associated with chronic phlegm, dyspnea and a doctor's diagnosis of asthma in childhood, was very strongly associated with a doctor's diagnosis of bronchitis and emphysema in adulthood. 16 This may be due to the fact that previous respiratory disease could have damaged the normal respiratory functions which may cause airway obstruction later, lead to breathlessness and asthma.…”
Section: Discussionmentioning
confidence: 97%
“…According to a case control study by Asfaw et al among pharmaceutical workers of Ethiopia the adjusted odds ratio for previous history of respiratory diseases was 3.36 for the development of chronic respiratory symptoms in the future. 15 The study done by Galobardes et al among the historical cohort of male students who attended Glasgow university between 1948 and 1968 also revealed that a history of bronchitis in early life was moderately associated with chronic phlegm, dyspnea and a doctor's diagnosis of asthma in childhood, was very strongly associated with a doctor's diagnosis of bronchitis and emphysema in adulthood. 16 This may be due to the fact that previous respiratory disease could have damaged the normal respiratory functions which may cause airway obstruction later, lead to breathlessness and asthma.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic respiratory symptoms were defined as the development of one or more of the symptom (s) of chronic cough, chronic phlegm, chronic wheezing, chronic shortness of breath, and chronic chest tightness which last (s) at least 3 months in 1 year. Detail definitions of each respiratory symptom were published elsewhere [1,2] and used in this study. The modified Medical Research Council (mMRC) Dyspnoea Scale was used as a measure of dyspnoea severity, ranged from 0 to 4, being 0 indicated no breathlessness and 4 indicated too breathless to leave the house.…”
Section: Operational Definitionsmentioning
confidence: 99%
“…Similarly, height was measured by using an erect height measuring device and approximated to 0.1 cm. Then, body mass index (BMI) of the study participants was calculated from their body weight and height using weight in kilogram / (height in meter) 2 as a formula [35].…”
Section: Data Collection Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study indicated the previous and family history of chronic obstructive respiratory disease, previous dusty working environment, and ever smoking were the main risk factors for chronic obstructive respiratory symptoms and its exacerbation [12]. Several risk factors like cigarette smoking, ambient particulate matter, household air pollution, occupational particulates, ozone, and second-hand smoke can cause COPD.…”
Section: Introductionmentioning
confidence: 99%